Antibacterial Activity of the Essential Oil From Litsea cubeba Against Cutibacterium acnes and the Investigations of Its Potential Mechanism by Gas Chromatography-Mass Spectrometry Metabolomics - Chen, Jing; Zhang, Jianing; Zhu, Longping; Qian, Chunguo; Tian, Hongru; Zhao, Zhimin; Jin, Lu; Yang, Depo (Frontiers in Microbiology, 2022)
Cutibacterium acnes (C.acnes) is an anaerobic Gram-positive bacterium generally considered a human skin commensal, but is also involved in different infections, such as acne and surgical infections. Although there are a variety of treatments, the side effects and the problem of bacterial drug resistance still limit their clinical usage. In this study, we found that essential oil (EO) distilled from fresh mature Litsea cubeba possessed promising antibacterial activity against C.acnes. In order to elucidate its potential mechanism, bacteriostatic activity test, Live/Dead kit assay, scanning electron microscope (SEM), transmission electron microscope (TEM) and metabolomics were employed. In addition, the content of ATP in bacterium and the activities of key enzymes involved critical metabolic pathways were detected using a variety of biochemical assays. The results showed that EO could destroy C.acnes morphology and inhibit its growth, which the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of EO were 400 μg/mL and 800 μg/mL, respectively. Moreover, results from our study showed that EO had a significant effect on the C.acnes normal metabolism, and 86 metabolites changed, which directly led to the impact of 34 metabolic pathways. The synthesis of ATP in bacterial cells was also severely inhibited, and the activities of key enzymes of the glycolysis and Wood-Werkman cycle were significantly affected (Pyruvate Carboxylase, Malate Dehydrogenase and Pyruvate kinase activities were decreased). Taken together, these results demonstrated that the bacteriostatic effect of EO against C.acnes by breaking the bacterial cell morphology and disrupting cell metabolism, including inhibition of key enzyme activity and ATP synthesis. The results from our study may shed new light on the discovery of novel drugs with more robust efficacy and fewer side effects.